(untitled) (Journal of Hama University, 2024)
The research aimed to identify the role of the Faculty of Information at Damascus University in achieving cultural sustainability from the point of view of graduate students. To achieve the research objectives, the researcher used the descriptive analytical method, designed a questionnaire consisting of (22) items in its final form, and applied it to a stratified random sample consisting of (80) postgraduate students, drawn by the researcher from the community consisting of (172) male and female students from Postgraduate students at the Faculty of Information at Damascus University. It was found that the role of the Faculty of Mass Communication in achieving cultural sustainability is average in general, and that its role in achieving human and media development is average. The research also found that there is no statistically significant difference between the average grades of the students due to the variable of the academic stage, and the presence of statistically significant differences between the average grades of the students due to the variable Specialization for the benefit of students specializing in radio and television; Therefore, the research recommended designing special curricula for Syrian Faculties of Mass Communication on thinking skills and self-learning, and seeking the assistance of the Faculty of Mass Communication at the University of Damascus from experienced faculty members in other Faculties of the University of Damascus in teaching thinking skills and self-learning subjects in the Faculty, and holding training workshops to develop the entrepreneurial skills of students. and those in charge of the College of Mass Communication at Damascus University reconsidered the curricula and college outcomes in a way that would contribute to graduating culturally qualified human cadres to better lead the Syrian Arab community in the media.